2018
DOI: 10.1177/0017896917751554
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health literacy on diabetes self-management education

Abstract: Background. Diabetes self-management education (DSME) is generally considered to be a key determinant of the treatment outcomes and related costs of diabetes mellitus. While DSME programmes generally have positive outcomes, their effects may depend on certain factors such as the type of programmes provided and patients' level of health literacy (HL). Low HL has been associated with poorer self-management behaviours and poor medication adherence in diabetic patients, but its impact on the effects of DSME has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…Significant differences in HL were found in relation to education. People with T2DM who had completed a university-level education reported a significantly higher HL (as measured by the HLS-Q12) than those with a lower education level, which is similar to the findings of previous studies [4,12,[53][54][55][56][57]. This finding was also supported when using the FCCHL to measure HL in the same population [11].…”
Section: Hl and Demographic Variables General Health Diabetes Outcosupporting
confidence: 87%
See 2 more Smart Citations
“…Significant differences in HL were found in relation to education. People with T2DM who had completed a university-level education reported a significantly higher HL (as measured by the HLS-Q12) than those with a lower education level, which is similar to the findings of previous studies [4,12,[53][54][55][56][57]. This finding was also supported when using the FCCHL to measure HL in the same population [11].…”
Section: Hl and Demographic Variables General Health Diabetes Outcosupporting
confidence: 87%
“…According to the proportion of responses in each response category, over one-third marked the HL tasks as difficult or very difficult, which implies that health professionals should pay attention to the individual's HL and should adapt their health communication to the appropriate level. In contrast to van der Heide [4] and Hussein, Almajran and Albatineh [53] but in accord with Al Sayah et al [16] and Vandenbosch et al [54], no significant differences in HL with regard to age were found. However, the average age of the sample was relatively high, so differences related to age may not have been evident.…”
Section: Hl and Demographic Variables General Health Diabetes Outcomentioning
confidence: 57%
See 1 more Smart Citation
“…To assess the effectiveness of ongoing treatment blood sugar should be regularly monitored. In our study we found that adherence to oral hypoglycemic drugs (86.52%) and insulin injections (78%) was high which is contrast with the findings of previous studies [23]. The reasons for nonadherance are multifactorial which includes age, perception, duration of disease, polutheraphy, psychological factors [24].…”
Section: Discussioncontrasting
confidence: 96%
“…In our study 69.5% checked the blood sugar every 3 month which is similar were observed to a study done in [22]. The level of education appeared to play a magnificent role in medication adherence in accordance with the previous studies [23]. To assess the effectiveness of ongoing treatment blood sugar should be regularly monitored.…”
Section: Discussionsupporting
confidence: 88%